Fiscal Adjustment for Stability and Growth - Daniel, James (Pamphlet Series; Pamphlet Series, ;, 2006)
The pamphlet (which updates the 1995 Guidelines for Fiscal Adjustment) presents the IMF's approach to fiscal adjustment, and focuses on the role that sound government finances play in promoting macroeconomic stability and growth. Structured around five practical questions-when to adjust, how to assess the fiscal position, what makes for successful adjustment, how to carry out adjustment, and which institutions can help-it covers topics such as tax policies, debt sustainability, fiscal responsibility laws, and transparency.